2022
DOI: 10.21037/atm-22-877
|View full text |Cite
|
Sign up to set email alerts
|

Pectic polysaccharides ameliorate the pathology of ulcerative colitis in mice by reducing pyroptosis

Abstract: Background: Ulcerative colitis (UC) is an inflammatory bowel disease which seriously affects the quality of life of patients. There has been an increasing amount of research related to the therapeutic effects and mechanisms of natural plant substances in the treatment of recurrent UC. Rauwolfia verticillata var.Hainanensis is a medicinal plant that is native to Hainan Island, China. Some studies have documented that pectic polysaccharides (PPs) from Rauvolfia inhibited the progression of colon ulcers. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The mechanism of UC is not fully understood and has been listed as a risk factor for the development of colorectal cancer. As a result, there is currently no specific effective drug for the treatment of UC ( 60 ). Intestinal mucosal immunity plays an important role in the occurrence and development of intestinal inflammation, and many components of the mucosal immune system, including lymphocytes and leukocytes, are closely related to the development of UC ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of UC is not fully understood and has been listed as a risk factor for the development of colorectal cancer. As a result, there is currently no specific effective drug for the treatment of UC ( 60 ). Intestinal mucosal immunity plays an important role in the occurrence and development of intestinal inflammation, and many components of the mucosal immune system, including lymphocytes and leukocytes, are closely related to the development of UC ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent findings suggested that both Caspase-1 and Caspase-11 activation possess the function to induce the release of IL-1β and IL-18, but only Caspase-1 could directly cleave them (Man and Kanneganti, 2015); in addition, epithelium IL-18 secretion was independent on NLRP3 but dependent on Caspase-1 (Song- Zhao et al, 2014). Numerous experimental studies on animals have demonstrated inhibiting Caspase-1-dependent pyroptosis could protect against DSS-induced colitis (Tian et al, 2020;Cui et al, 2022;Xue et al, 2022). In view of this, we observed the regulation effect of SIT on inflammatory mediators in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings suggested that both Caspase-1 and Caspase-11 activation possess the function to induce the release of IL-1β and IL-18, but only Caspase-1 could directly cleave them (Man and Kanneganti, 2015); in addition, epithelium IL-18 secretion was independent on NLRP3 but dependent on Caspase-1 (Song- Zhao et al, 2014). Numerous experimental studies on animals have demonstrated inhibiting Caspase-1-dependent pyroptosis could protect against DSS-induced colitis (Tian et al, 2020;Cui et al, 2022;Xue et al, 2022). In view of this, we observed the regulation effect of SIT on inflammatory mediators in our present study.…”
Section: Discussionmentioning
confidence: 99%